Упростите выражение: 1) 3c+a/4c - a-7c/4c                                       2) 2p/p+3 + 3-p/p+3                                       3) x^2/x-4 + 4x/4-x                                       4) m/m^2-n^2 - n/m^2-n^2

Упростите выражение: 1) 3c+a/4c - a-7c/4c                                        2) 2p/p+3 + 3-p/p+3                                        3) x^2/x-4 + 4x/4-x                                        4) m/m^2-n^2 - n/m^2-n^2
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{3c+a}{4c}-\frac{a-7c}{4c}=\frac{3c+a-a+7c}{4c}=\frac{10c}{4c}=2,5[/latex] [latex]\frac{2p}{p+3}+\frac{3-p}{p+3}=\frac{2p+3-p}{p+3}=\frac{p+3}{p+3}=1[/latex] [latex]\frac{x^2}{x-4}+\frac{4x}{4-x}=\frac{x^2-4x}{x-4}=\frac{x(x-4)}{x-4}=x[/latex] [latex]\frac{m}{m^2-n^2}-\frac{n}{m^2-n^2}=\frac{m-n}{m^2-n^2}=\frac{m-n}{(m-n)(m+n)}=\frac{1}{m+n}[/latex]
Гость
1)(3c+a)/4c -(a-7c)/4c=((3c+a-a+7c)/4c=10c/4c=2,5 2)2p/(p+3) +(3-p)/(p+3)=(2p+3-p)/(p+3)=(p+3)/(p+3)=1 3)x²/(x-4)+4x/(4-x)=(x²-4x)/(x-4)=x(x-4)/(x-4)=x 4)m/(m²-n²)-n/(m²-n²)=(m-n)/(m-n)(m+n)=1/(m+n)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы